Higher Education in Post-Conflict Conditions - Pacheco, Ivan F; Turner Johnson, Ane (International Higher Education, 2014)
The connection between higher education and peacebuilding remains largely uncharted. This article explores how internal armed conflicts have affected higher education institutions in Colombia and Kenya and their ability to promote peacebuilding. Despite the differences in context and the evolution of the conflicts, in both countries the transformation efforts started during the conflict stage.